2015
DOI: 10.1177/2165143414565837
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Services for Youth With Emotional Disturbances in and After High School

Abstract: This study uses data from the National Longitudinal Transition Study–2 to examine the rates at which youth with emotional disturbances received services during and up to 8 years after high school. Parents’ efforts to obtain services, information sources accessed, problems encountered, and the perceived sufficiency of services to meet youths’ needs are described. Findings show a drop in receipt rates for several services in the first 2 years post high school, relative to those received during high school, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Exploring multiple perspectives helps inform mental health professionals and youth development program practitioners of the areas where allocation of services and funding can be most valuable to transition-age youth with SED (Goodcase et al, 2021 ; Kaufman et al, 2019 ; LaPorte et al, 2014 ; Lich et al, 2017 ). The five clusters, or themes, that emerged from participant responses in our study echo the existing literature on barriers to adult mental health services (Klodnick et al, 2021 ; LaPorte et al, 2014 ; Wagner et al, 2016 ) and other challenges experienced by youth with SED in the transition to adulthood (Akinola & Dunkley, 2019 ; Marion & Paulsen, 2019 ; Walters, 2017 ; Xie et al, 2014 ). At the same time, our findings reflect literature on adolescent mental health services and positive youth development that emphasize the importance of youth experiences and participation in service evaluation and planning (Brown, 2006b ; Chauveron et al, 2021 ; Delman & Jones, 2002 ; LaPorte et al, 2014 ; Lich et al, 2017 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Exploring multiple perspectives helps inform mental health professionals and youth development program practitioners of the areas where allocation of services and funding can be most valuable to transition-age youth with SED (Goodcase et al, 2021 ; Kaufman et al, 2019 ; LaPorte et al, 2014 ; Lich et al, 2017 ). The five clusters, or themes, that emerged from participant responses in our study echo the existing literature on barriers to adult mental health services (Klodnick et al, 2021 ; LaPorte et al, 2014 ; Wagner et al, 2016 ) and other challenges experienced by youth with SED in the transition to adulthood (Akinola & Dunkley, 2019 ; Marion & Paulsen, 2019 ; Walters, 2017 ; Xie et al, 2014 ). At the same time, our findings reflect literature on adolescent mental health services and positive youth development that emphasize the importance of youth experiences and participation in service evaluation and planning (Brown, 2006b ; Chauveron et al, 2021 ; Delman & Jones, 2002 ; LaPorte et al, 2014 ; Lich et al, 2017 ).…”
Section: Discussionsupporting
confidence: 74%
“…Adolescents who receive mental health services experience a steep decline in both quality and the number of services available once they turn 18 years-old and lose eligibility (Osgood et al, 2010 ; Singh, 2009 ). Within the first two years of leaving high school, youth with SED receive fewer services than when enrolled and continue to experience a decline in services thereafter (Wagner et al, 2016 ). Two important factors contributing to unsuccessful transitions between child and adult mental health services are availability and overall developmental appropriateness of adult mental health services (Davis & Munson, 2018 ; Paul et al, 2013 ).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…To ensure a positive collaboration, it is important to develop knowledge of the local resources and partners, ensure that the information about these resources is easily available to youth and their families, formally include partners in the development of the intervention plan and specify roles and responsibilities of each partner involved with the student. To ensure an efficient collaboration, participants suggest identifying a transition co‐ordinator, a recommendation also make by several researchers in this field (Crompton & Bond, 2022; Jacob et al., 2022; Lillis & Kutcher, 2021; Noonan et al., 2012; Poirier et al., 2020; Scheef & Mahfouz, 2020; Wagner et al., 2016). For example, this co‐ordinator can be a school professional who has the mandate to overview the transition to adulthood plan for a student but who does not necessarily provide direct service to them.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor and Henninger (2015) found that adolescents with autism with lower adaptive behavior scores and more severe autism symptoms received more services. In the post-school years as well, there appears to be a decline in receipt of services for students requiring fewer adaptive supports (Taylor & Seltzer, 2011; Wagner et al, 2016). Similarly, Baer et al (2011) found that students with high-incidence disabilities (e.g., learning disabilities, attention-deficit hyperactivity disorder [ADHD]) had less access to post-school services than those with ID.…”
mentioning
confidence: 99%